Anatomy and Physiology Laboratory Manual for Nursing and Allied Health - Marz, Aylin; Kamatchi, Ganesan; D'Silva, Joseph; Prabhakaran, Krishnan; Chandra, Rajeev; Isekeije, Solomon (Open textbook library., 2020)
Authors’ Institution: Norfolk State University, Norfolk, VA, USA Funding: Virtual Library of Virginia (VIVA) Course Redesign Grant, 2020 – 2023